Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review - Page 749: 138



Work Step by Step

$(\sqrt 6-9i)(\sqrt 6+9i)$ =$(\sqrt 6)^{2}-(9i)^{2}$ =$6-81i^{2}$ =$6-81(-1)$ =$6+81$ =$87$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.